EVALUASI PENGGUNAAN LAHAN DI DAERAH TANGKAPAN AIR (DTA) DANAU BUATAN RUMBAI KOTA PEKANBARU - Nenny Indrawaty; Aras Mulyadi; Zulkarnain Zulkarnaini (Program Pascasarjana Universitas Riau, 2016)
Evaluation of land capability is a way to use the land (land resources) in accordance with its potential. Land potential assessment is needed, especially in policy development, land use and sustainable land management. The purpose of this study was to evaluate the land use based on the land capability at Danau Buatan Rumbai cathment area, erosion predicting on land use and assess soil and water conservation that can be applied in Danau Buatan Rumbai cathment area. The results of this study indicate that the land use in Danau Buatan Rumbai cathment area according to the land capability (class II, III and IV). The results of erosion prediction is greater than the erosion tolerable (ETol), this suggests that the land use in this area there is no soil conservation efforts. Suggested land use planning is the land for oil palm plantations, rubber plantations and mixed farms require conservation efforts bench terracing, contour planting, soil cover crops and waterways. Agricultural land crops require conservation efforts bench terracing, gulud terracing, mulch crop residues, rotation and crop rotation. The land requiring conservation cover crops and grass canals. Land for residential conservation efforts need to planting trees and ground cover plants. and shrub lands conservation efforts allowed the meeting to be a scrub.